The effect of different production systems on the content of micronutrients and trace elements in potato tubers - Jadwiga Wierzbowska; Bogumił Rychcik; Arkadiusz Światły (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2018)
The aim of this study was to determine the effect of different production systems (conventional, integrated and organic) on the content of micronutrients and trace elements in the tubers of very early, early and medium-early maturing potato cultivars. Five Polish potato cultivars were grown in three production systems under field conditions. In plant material selected microelements (chemical elements essential for living organisms) were analysed: boron (B), copper (Cu), iron (Fe), manganese (Mn) and zinc (Zn) as well as some trace elements (not regarded as essential element for living organisms): chromium (Cr), nickel, (Ni) and lead (Pb). The content of micronutrients and trace elements in potato tubers was modified by production system, genotype and weather conditions during the growing season. Organically grown potatoes had a higher content of B (8.6–8.9 mg kg−1) and Cu (2.8–3.1 mg kg−1), and a lower content of Fe (47.0–47.1 mg kg−1), Mn (6.0–6.4 mg kg−1) and Zn (11.9–12.2 mg kg−1), than potatoes grown in conventional and integrated systems. Potatoes grown in the conventional system had the highest Pb content. Organic cultivation can assure better alimentation of potato tubers with B and Cu, which are important microelements often deficient in the soils. On the contrary, when cultivating potato in conventional system, one should supply this element with fertilisers.